PROBLEMS OF SUSTAINABLE MOBILITY IN POLISH CITIES - Korneć, Radosław (Management and Administration Journal, 2024)
Sustainable mobility in Polish cities faces numerous challenges arising from dynamic urbanization, demographic changes, and the growing transportation needs of residents. The increase in the number of cars on urban roads leads to congestion, air pollution, and a decrease in quality of life. Transport policies must focus on reducing individual car traffic in favour of public transport, micromobility, and eco-friendly solutions. Key initiatives include creating bike paths, promoting electric scooters, and developing zero-emission vehicles. Financial support, infrastructure modernization, and changing social attitudes toward transport are essential to achieve sustainable mobility. These actions must be supported by local and governmental strategies such as the "European Green Deal" and the "Sustainable and Smart Mobility Strategy." Furthermore, educating the public and engaging residents in transport planning will contribute to improving the quality of urban life and the environment.